Sac and Fox Agency letter books - Beach, John, 1812-1874 (1840)
Collection contains letters sent between June 23, 1840 and August 5, 1847 by agent John Beach of the Sac and Fox Agency to T. Hartley Crawford (Commissioner of Indian Affairs), Joshua Pilcher (Superintendent of Indian Affairs in St. Louis) and others.